EVALUATION INSTRUMENTS OF COMPREHENSIVE GUIDANCE AND COUNSELING PROGRAM IN THE CULTURE OF HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Setiawati, Atie; Suherman A.S, Uman; Rusmana, Nandang (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
Program evaluation in comprehensive guidance and counseling is very important to determine the level of goal achievement. For the evaluation results to provide the right information, a valid and reliable instrument is needed. At the higher education level, the comprehensive guidance and counseling program, including the program evaluation component, does not have many references that users can refer to. The available references focus more on primary and secondary education levels. This research is intended to produce the intended evaluation instrument. Descriptive methods and literature reviews were used in this study. The data were revealed using a Delphi technique questionnaire involving three experts, then analyzed qualitatively and quantitatively. In this study, the constructs of evaluation instruments for comprehensive guidance and counseling programs were synthesized and modified from various expert opinions and professional organizations with two patterns of answers: yes and no. The resulting evaluation instrument needs to be empirically tested for its feasibility by involving adequate participants.